Value creation in projects: Towards a narrative perspective. Issue 5 (July 2019) - Green, Stuart D.; Sergeeva, Natalya
Abstract: It is contended that value is a social construct, and that the processes of social construction are rooted in language. On this basis we argue that value creation is a process which lends itself to interpretation from a narrative perspective. Previous attempts at value creation have been promoted under the label of 'value management'. There are two approaches which are identifiable in the literature. The first is based on the traditional narrative of value engineering (aka Hard VM) and is primarily directed towards cost reduction. The second more recent variant is labelled 'soft' value management (Soft VM) and is primarily directed towards the achievement of a shared understanding of the value criteria relating to an individual project. The two approaches are critiqued in terms of their underlying assumptions and it is suggested that they are best understood as different forms of narrative. The emerging literature on value creation is similarly critiqued in accordance with the adopted narrative perspective. The distinction is made between formalised narratives of value on the level of the organisations involved in the project coalition and the anecdotal stories which individuals use to make sense of their own lived experiences. Emphasis is given to the ways in which different narratives interact, and to the way in which they remain contestable over time. Particular attention is given to the confluence between storytelling and identity work. Highlights: Value is in essence a social construct, and the processes of social construction are rooted in language Value creation in projects is a process which lends itself to interpretation from a narrative perspective There has been shifts in understanding value creation in projects: from 'hard' value engineering to 'soft' value management Narratives of value on the level of the organisations interact with anecdotal stories which individuals use to make sense of their lived experiences Personal values are inherently inseparable from 'identity work'